Technologies of psychological support for the subjective well-being of military servicemen - KHARYTYNSKYІ, Andriy (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2024)
Background. This article analyzes psychological technologies designed to support individual subjective well-being, developed and tested by Ukrainian and foreign scholars across various fields. The purpose of this article is to explore modern psychological technologies aimed at enhancing the subjective well-being of individuals within Ukraine's security and defense forces. This involves analyzing and systematizing scientific approaches to understanding the characteristics of psychological support of individual's subjective well-being and assessing applied psychological technologies, their components, methods, directions, and practices in the research of Ukrainian and foreign scientists.Results. To optimize and enhance personal well-being across various activities, diverse methods, directions, and techniques of psychological work are found to be effective. These include: cognitive-behavioral psychotherapy, gestalt therapy, body-oriented therapy, positive and transcultural psychotherapy, positive psychological interventions (both cognitive and behavioral), therapies aimed at increasing mental stability in the workplace, fostering resilience in adults facing life and professional challenges, therapy focusing on retrospective and proactive life experience reviews, meditation techniques promoting self-regulation and eudemonistic well-being, ecological therapy employing therapeutic rest methods, coaching technologies, and training in various self-help measures and techniques.Conclusions. It has been established that providing psychological support for the subjective well-being of military personnel should occur within the framework of positive psychology. This approach ensures a clear understanding of the developmental processes related to leading a purposeful and meaningful life across various spheres, utilizing scientifically measured, manageable components: positive emotions, interaction, relationships, meaning, and accomplishments. The components, methods, and approaches researched and described regarding psychological work to support the subjective well-being of military personnel can be effectively integrated into comprehensive professional and psychological training.
Keywords: subjective well-being; psychological support; psychological technologies; professional psychological training; psychological resources; extreme conditions; the identity of a serviceman